How do Stakeholders Participate in Waste and Water Security Management? Insights from West Java Province, Indonesia - Taryono, Ono; Sufianti, Ely; Jubaedah, Edah (Jurnal Borneo Administrator, 2025)
In collaborative governance, participation is essential to encourage all stakeholders to participate in decision-making. This paper aims to explore the empirical state of stakeholder participation in waste and water security management. Using the qualitative method, the stakeholders are analysed based on the penta-helix criteria,their roles, and participation during the stages of the projects. Having conducted deep observations, interviews, and document reviews of various sources, the research findings reveal that one stakeholder, the government or public sector, plays a dominant role in waste and water security management. In contrast, the other four stakeholders, such as the business sector, academia, media, voluntary organizations, and the community demonstrate limited participation. This research suggests to emphasize the need for a multi-stakeholder approach by developing an inclusive and participatory governance structure in the form of advisory board, working groups or consultative forums, enhancing the stakeholder capacity through knowledge sharing,workshops, and technical support to strengthen stakeholder’s competencies in strategic planning, project management, and evaluation methodologies, and strengthening policy framework that explicitly outlines the roles and responsibilities of each stakeholder